Attention to eSports advertisement : effects of ad animation and in-game dynamics on viewers’ visual attention - Seo, Young-Nam (2020)
ESports refers to professional video gaming that is typically broadcasted with a live commentary on TV or the Internet. Despite the rapid growth of eSports industry and its potential for a valuable advertising platform, there has not been much discussion about effective advertising strategies for the placement of virtual ads in eSports. Based on previous research, one advertisement factor (i.e. ad animation) and one in-game factor (i.e. in-game dynamics) are identified and tested in an experiment (N = 116) with a 2 (ad animation: static vs. animated ads) × 2 (in-game dynamics: battle vs. non-battle scenes) mixed design. The results show that both ad animation and in-game dynamics have a significant impact on viewers’ visual attention, in terms of fixation count and duration measured by an eye-tracking device. The results also show a significant interaction in which the impact of ad animation on fixation duration is more magnified when in-game play is less busy (i.e. non-battle scenes), compared to when it is busy (i.e. battle scenes). Theoretical implications based on the limited-capacity model, as well as practical implications for practitioners are discussed.